Technical evaluation of different respiratory monitoring systems used for 4D CT acquisition under free breathing. (8th March 2015) - Heinz, Christian; Reiner, Michael; Belka, Claus; Walter, Franziska; Söhn, Matthias
Abstract : Respiratory monitoring systems are required to supply CT scanners with information on the patient's breathing during the acquisition of a respiration‐correlated computer tomography (RCCT), also referred to as 4D CT. The information a respiratory monitoring system has to provide to the CT scanner depends on the specific scanner. The purpose of this study is to compare two different respiratory monitoring systems (Anzai Respiratory Gating System; C‐RAD Sentinel) with respect to their applicability in combination with an Aquilion Large Bore CT scanner from Toshiba. The scanner used in our clinic does not make use of the full time dependent breathing signal, but only single trigger pulses indicating the beginning of a new breathing cycle. Hence the attached respiratory monitoring system is expected to deliver accurate online trigger pulse for each breathing cycle. The accuracy of the trigger pulses sent to the CT scanner has to be ensured by the selected respiratory monitoring system. Since a trigger pulse (output signal) of a respiratory monitoring system is a function of the measured breathing signal (input signal), the typical clinical range of the input signal is estimated for both examined respiratory monitoring systems. Both systems are analyzed based on the following parameters: time resolution, signal amplitude, noise, signal‐to‐noise ratio (SNR), signal linearity, trigger compatibility, and clinical examples. The Anzai system shows a better SNR ( ≥ 28   dB ) than the Sentinel system ( ≥ 14.6   dB ). In terms of compatibility with the cycle‐based image sorting algorithm of the Toshiba CT scanner, the Anzai system benefits from the possibility to generate cycle‐based triggers, whereas the Sentinel system is only able to generate amplitude‐based triggers. In clinical practice, the combination of a Toshiba CT scanner and the Anzai system will provide better results due to the compatibility of the image sorting and trigger release methods. PACS numbers: 87.57.Q‐, 07.07.Df